Pattern and treatment of Vitiligo at Tertiary health care level in Dhaka city - Shuma, Madhabi Lata; Halder, Shimul; Rahman, Md Motiur (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The etiopathogenesis of depigmentation in vitiligo is still obscure that constitutes a major psychological health problem in Bangladesh. So our sociodemographic study represents the pattern and treatment of vitiligo at tertiary level of healthcare in Dhaka city. It has helped to identify the drugs used for the treatment of this disease. A total of 100 (70 male and 30 female) patients were interviewed at the Department of Dermatology and Venereology in Bangabandhu Sheikh Mujib Medical University Hospital (BSMMUH) to conduct the study. It was observed that, the urban (62%) and upper-middle class people (55%) were most commonly affected by the disease. The most common signs of vitiligo were pale skin (45%) and itching (26%) and the drugs used to manage vitiligo were mainly methoxsalen (83%), riboflavin (53%), tacrolimus (49%), zinc sulphate B.P. (52%), tri-methyl solaren (55%), pimecrolimus (42%) and monobenzone (12%). Our population-based data provided evidence for a protective effect of vitiligo and supported the purported protective role against this disease. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21870 Dhaka Univ. J. Pharm. Sci. 13(1): 93-96, 2014 (June)